Caring for and Protecting each Other: Peers and Gender-related Participation in and outside School - Köhler, Sina-Mareen; Winkler, Anna Lena (SocietàMutamentoPolitica, 2025)
This article explores the participation experiences of 12- to 16-year-olds both in and outside of school, with a focus on how young people engage with gender-related topics in peer interactions. We present data from our longitudinal study which investigates peer relationships and participation during the COVID-19 pandemic, working with qualitative interviews, which are analyzed using the documentary method. By adopting a broad understanding of participation the study emphasizes the importance of empirical research on youth participation beyond formal political contexts. This framework enables a detailed analysis of the contexts, actors, and practices of youth participation, highlighting the role of peer relationships in gender discussions. In the school setting, the article examines practices such as student representation, complaints, and the expression of opinions on gender and LGBTQ* topics. Outside of school, it focuses on extracurricular activities and the negotiation of gender identity within personal contexts, such as family and romantic relationships. The findings demonstrate how young people assert and defend gender-related claims relevant to their social participation, showing the crucial role of peer support in navigating gender struggles both privately and publicly. Ultimately, the article illustrates how peer groups provide emotional and discursive support as adolescents navigate their gender identities across different environments.